A Simple Algorithm for the Inframammary Fold Reconstruction, Balcony-Like Technique. Issue 3 (September 2019) - Cannistrà, Claudio; Trivisonno, Angelo; Deschler, Alexis; Aboud, Celine; Shiffman, Melvin A.; Monti, Massimo
The inframammary fold (IMF) is one of the most important landmarks that defines the breast region. Most of the current IMF reconstructive techniques are based on the creation of fibrotic structures to maintain the breast. We present a surgical technique of IMF reconstruction by the creation of a fascial flap underpinned by an anatomical evaluation of this structure and a simple algorithm to define the localization of the new IMF. Fifteen patients underwent our procedure of IMF reconstruction from 2004 to 2016. The patients were followed during at least 6 months after IMF reconstruction. This technique is based on the creation of a pectoralis major fascial flap fixed to the dermis by inverted resorbable sutures. The fascial flap represents a new ligament of the IMF reconstituting a physiological support. Cosmetic outcomes and stability over time were assessed. The long-term aesthetic outcome is optimal on all the patients treated with a natural shape and a good definition of the new IMF. There were no noted complications or revision surgery during the follow-up. Our technique consists of an anatomical reconstitution of IMF recreating a natural support "balcony-like" formed by the pectoralis fascia fixed to the dermis. This technique is useful to correct reconstructive or aesthetic procedures of the breast, with great cosmetic outcome and high reliability underpinned by the use of our position algorithm which is easy to use and enables a symmetrical position of the IMF.